Combination of dimethylmethoxy chromanol and turmeric root extract synergically attenuates ultraviolet‐induced oxidative damage by increasing endogenous antioxidants in HaCaT cells - Wang, Qianqian; Zhong, Ye; Li, Nihong; Du, Le; Ye, Rui; Xie, Yicheng; Hu, Fan (Skin research and technology, 2023)
Background Repeated exposure to UV generates excessive reactive oxygen species (ROS) and damages the enzymatic antioxidant defense system including quinone oxidoreductase 1 (NQO1) and superoxide dismutase (SOD) in skin. Topical application of antioxidants may prevent the undesired damage of cellular proteins, lipids and DNA in skin. Dimethylmethoxy chromanol (DMC) is a bioinspired molecule, designed to be a structural analog to the γ–tocopherol that is naturally present in vegetables and plants. Turmeric root extract (TRE) is from a plant in South Asia extensively used as a food spice & vegetable, and its main components are turmerones. As both DMC and TRE are strong antioxidants with complementary antioxidation mechanisms, the aim of this study was to investigate the enhanced protective effects of their combination on oxidative damage in HaCaT cells following UVB exposure. Materials and methods The effects of single and combined administrations of DMC and TRE on the SOD activity of HaCaT cells were evaluated by the SOD assay and qPCR. The NQO1 expression in the UVB‐treated HaCaT cells was analyzed by the Western Blot. Furthermore, a clinical test involving 24 subjects was conducted to evaluate the in vivo antioxidation efficacies of the serum formulated with the combination of DMC and TRE at the optimal weight ratio. Results SOD assay showed that pretreating DMC or TRE alone could not preserve the impaired HaCaT SOD activity after UVB treatment. DMC and TRE at 1:1 weight ratio was the optimal combination to enhance the HaCaT SOD activity by approximately more than 1‐fold compared with either of the single treated groups. No enhancement effect was observed at other mixing ratios. The 1:1 weight ratio was further proved to be optimal as this combination boosted the NQO1 expression by more than 50%, whereas no boosting effect was observed at other mixing ratios. The clinical test of the serum containing this optimal antioxidant combination demonstrated promising in vivo antioxidation efficacies after 4‐week use, including 7.16% improvement in skin lightening, 18.29% reduction in skin redness, 35.68% decrease in TEWL, 19.05% increase in skin gloss and 32.04% enhancement in skin firmness. Conclusion Collectively, our results indicated that the combination of DMC and TRE at 1:1 weight ratio attenuated the UV‐induced oxidative damage by synergistically boosting endogenous antioxidant enzyme activity in HaCaT cells. Therefore, this optimal antioxidant combination is a promising treatment to boost skin antioxidation defense system.